LISTENING MATERIALS IN ENGLISH TEXTBOOK: QUALITY REVIEW - Shabrina Ikbar; Hermansyah Hermansyah; Evi Rosmiyati (Universitas PGRI Palembang, 2023)
The objective of this study was to assess the quality of listening materials in the English textbook